Recurrent carpal tunnel syndrome associated with extension of flexor digitorum muscle bellies into the carpal tunnel: A case series - Rochelle Castillo; Khushboo Sheth; Alan Babigian; Christopher Scola (Archives of Plastic Surgery, 2018)
While the success or failure of carpal tunnel release ultimately depends on the interplay of a wide array of factors, a broad understanding of the normal anatomy of the carpal tunnel accompanied by awareness of the possible variations of the individual structures that make up its contents is crucial to optimizing surgical outcomes. While anatomic variants such as extension of the flexor digitorum muscle bellies have been described as a cause of primary carpal tunnel syndrome (CTS), there have been no reports depicting its association with recurrent CTS following initially successful carpal tunnel release, a finding with potentially significant prognostic implications that can aid in operative planning. In such cases where muscle extension is identified preoperatively, careful debulking of the muscle belly may be beneficial in improving long-term surgical outcomes.